Competitive Strategies of New Ports in a Multi-Facility Environment - Malau, April Gunawan; Barasa, Larsen; Simanjuntak, Marihot (Jurnal Abdidas, 2024)
In a dynamic landscape of global trade, the competitiveness of ports is paramount. This research explores the strategies employed by emerging ports to establish themselves amidst established facilities. Through qualitative interviews and descriptive analysis, the study delves into key factors driving port success, including infrastructure investment, operational efficiency, geographic advantage, service portfolio diversification, and marketing prowess. Additionally, it evaluates aspects like financial viability, environmental sustainability, regulatory compliance, technological innovation, human capital development, and risk management. Findings reveal that successful new ports prioritize advanced technology, streamlined processes, strategic locations, specialized services, effective branding, and robust financial management. They also emphasize environmental responsibility, regulatory adherence, innovation adoption, talent cultivation, and risk mitigation. By comprehensively analyzing these elements, this research offers insights crucial for new ports seeking to navigate and thrive within the complex web of port competition.